2019
DOI: 10.1111/pedi.12897
|View full text |Cite
|
Sign up to set email alerts
|

Inequalities in glycemic control in childhood onset type 2 diabetes in England and Wales—A national population‐based longitudinal study

Abstract: Background Not much is known about glycaemic‐control trajectories in childhood‐onset type 2 diabetes (T2D). We investigated characteristics of children and young people (CYP) with T2D and inequalities in glycemic control. Methods We studied 747 CYP with T2D, <19 years of age in 2009‐2016 (from the total population‐based National Pediatric Diabetes Audit [>95% diabetes cases in England/Wales]). Linear mixed‐effects modeling was used to assess socioeconomic and ethnic differences in longitudinal glycated hemoglo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Laura et al. (Khanolkar et al., 2019) conducted a study in 104 patients and found that family disorder was not conducive to HbA1c control in patients at 6‐month follow‐up (β = .46, p < .01). Good family support was beneficial for blood glucose control, and maternal affinity personality was beneficial for lowering HbA1c levels.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Laura et al. (Khanolkar et al., 2019) conducted a study in 104 patients and found that family disorder was not conducive to HbA1c control in patients at 6‐month follow‐up (β = .46, p < .01). Good family support was beneficial for blood glucose control, and maternal affinity personality was beneficial for lowering HbA1c levels.…”
Section: Resultsmentioning
confidence: 99%
“…Laura et al (Khanolkar et al, 2019) conducted a study in 104 patients and found that family disorder was not conducive to HbA1c…”
Section: Eunice Et Al's Studymentioning
confidence: 99%
“…Youth onset T2D disproportionately affects youth facing structural disadvantages, including living in poverty, 16,18,163,164,242 in food insecure households, and being a racialized minority. 243,244 In this context, mental health comorbidities including depression and anxiety are frequent among youth living with T2D.…”
Section: Psychosocial Healthmentioning
confidence: 99%
“…There is an over representation of deprivation with 45% of cases drawn from the most deprived backgrounds ( Fig. 1 ), a number that has not changed over the last 4 years [ 18 , 44 ].
Fig.
…”
Section: Epidemiology Of Types 1 and 2 Diabetes Mellitusmentioning
confidence: 99%